Polarização discursiva nas relações de alteridade no facebook: uma análise semiolinguística de interações polêmicas - Lago, Kaian (2024)
This study thematizes the relationships of otherness on Facebook in circumstances of discursive polarization arising from controversial interactions, through a semiolinguistic analysis of the way in which ideological positions, anchored in false truths, stereotypes and/or social imaginaries, can affect the contractual characteristics of the language act. Given this, the general objective of the research is to describe and analyze how language acts are staged in comment interactions on Facebook, through discursive polarization in relationships of otherness in the case of controversy. Three theoretical axes are used for the methodological-analytical application to the research in this study: the Dialogical Theory of the Bakhtin Circle (2010a, 2010b, 2016, 2017, 2020); the Argumentative Rhetoric of Ruth Amossy (2017, 2022); and, mainly, Patrick Charaudeau's Semiolinguistic Theory (2004, 2005, 2010, 2016, 2019, 2022). The research corpus is composed of four clippings of comment interactions from a Facebook post, from February 2022, which discuss an act by a municipal teacher in the city of Sapiranga (RS) who presented her students with a pencil accompanied by a red star - an act interpreted as party political propaganda by some recipients -, constituting controversial interactions. The research, of an applied nature, is exploratory and explanatory in terms of the objectives, bibliographic and documentary regarding technical procedures and qualitative regarding the approach to its problematization. The results obtained demonstrate that controversial interactions in Facebook comments, when permeated by discursive polarization, govern two distinct poles of semiotization of the world that evoke different refractions of the ideological sign through two sets of antagonistic ethical acts. These responsive refractions determine the acceptance or refusal of the established communication contracts and their particularities - defined by the discursive strategies and aims -, just like the disposition of the four subjects in the language act guided by the communication situation. When these refractions are based on the stereotypical recurrence of social imaginaries with a conspiracist background, they promote a radicalization of polarization that causes the compromise of alteritarian relationships in the communication contract, based on the breach of expectations in the face of opposition manifested by the most varied mistruths identified.